Executing Power Distribution System Using Geographic Information System - Kalyan Chakravarti Yelavartim, Ramesh Mande (International Journal of Advanced Science and Technology, 2020)
Electricity is an important want for our standard of living. Power distribution ought to be managed safely and productively by power distribution firms. Efficient functioning of Distribution Company ends up in the event of power sector and economy. Power distribution system is benefited way more with the evolution of package and IT sector. This paper shows the appliance of latest and rising technology like GIS that plays a significant role in trendy management of power distribution firms. GIS works with knowledge on associate degree interactive map wherever it may be updated, understood, and shared.GIS integrates each land base and also the electrical network maps.GIS isn’t solely helpful in up internal potency levels referring to power offer watching, developing correct information, industrial and client services however conjointly very helpful for necessary functions like facility management, energy audit, network analysis, bother decision management, load management, thievery detection etc..